Tax competition and tax revenues - Alfred Boss (Kiel Institute for World Economics (IfW), 2005)
It is often feared that tax competition might lead to a "race to the bottom". The consequence of a decline of tax rates on capital income would be shrinking capital income tax revenues and difficulties for national governments to perform their usual tasks. The paper analyzes what happened to tax revenues in a lot of OECD countries. It turns out that taxes on capital income contribute to the financing of public expenditures in a more or less unchanged extent; in addition, there are no significant changes of the level and the structure of total tax revenues.
Keywords: H20; H87; 330; Race to the bottom; Income tax revenues; Tax competition; Steuerwettbewerb; Kapitalertragsteuer; Steueraufkommen; Körperschaftsteuer; OECD-Staaten